2020
DOI: 10.1177/1533033820947489
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone and Difluoromethylornithine (DFMO) Synergistically Induce Apoptosis of Human Acute T Lymphoblastic Leukemia Jurkat Cells Through the Modulation of Epigenetic Pathways

Abstract: Thymoquinone (TQ), a natural anticancer agent exerts cytotoxic effects on several tumors by targeting multiple pathways, including apoptosis. Difluoromethylornithine (DFMO), an irreversible inhibitor of the ornithine decarboxylase (ODC) enzyme, has shown promising inhibitory activities in many cancers including leukemia by decreasing the biosynthesis of the intracellular polyamines. The present study aimed to investigate the combinatorial cytotoxic effects of TQ and DFMO on human acute T lymphoblastic leukemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…UHRF1 has been reported to be a target of several natural compounds or derivatives that exhibit anticancer properties by downregulating UHRF1. These compounds include TQ [ 11 , 12 , 23 , 60 , 61 , 62 , 63 ], curcumin [ 134 ], epigallocatechin-3-gallate [ 24 , 135 ], anisomycin [ 136 ], dihydroartemisinin [ 40 ], emodin [ 137 ], hinokitiol [ 33 ], shikonin [ 138 ], and luteolin [ 139 , 140 ], which can all upregulate many TSGs. Of these natural products, epigallocatechin-3-gallate and TQ have been shown to specifically target the SRA and RING domains of UHRF1, respectively.…”
Section: Uhrf1 Is a Main Target Of Natural Compounds Exhibiting Anticancer Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…UHRF1 has been reported to be a target of several natural compounds or derivatives that exhibit anticancer properties by downregulating UHRF1. These compounds include TQ [ 11 , 12 , 23 , 60 , 61 , 62 , 63 ], curcumin [ 134 ], epigallocatechin-3-gallate [ 24 , 135 ], anisomycin [ 136 ], dihydroartemisinin [ 40 ], emodin [ 137 ], hinokitiol [ 33 ], shikonin [ 138 ], and luteolin [ 139 , 140 ], which can all upregulate many TSGs. Of these natural products, epigallocatechin-3-gallate and TQ have been shown to specifically target the SRA and RING domains of UHRF1, respectively.…”
Section: Uhrf1 Is a Main Target Of Natural Compounds Exhibiting Anticancer Propertiesmentioning
confidence: 99%
“…Of particular interest to this review is that several studies have now shown that TQ can target the epigenetic reader UHRF1 as well as its partners, the epigenetic writers (DNMT1 and G9A) and erasers like HDAC1 [ 23 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that thymoquinone (TQ), the bioactive compound of black seed oil, has inhibitory effects on several cancers through the targeting of several signaling pathways [ 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ], including the reactivation of the p73 protein in p53-mutated tumors [ 136 , 160 , 161 ]. Recently, TQ was proposed to increase the expression of the p73 protein in a p53-mutant acute lymphoblastic leukemia cell line (Jurkat cells) by targeting the expression of various E3 ubiquitin ligases for p73, including Itch, Mdm2, FBXO45, and TRIM32 [ 62 ].…”
Section: Targeting Post-translational Modifications Of P73 For Cancer Therapymentioning
confidence: 99%
“…Firstly, it was approved by FDA in the treatment of human African trypanosomiasis (sleeping sickness) (ornidyl1, United States) ( Pepin et al, 1987 ), as a hair growth retardant in female facial hisrutism (Vaniqa; Allergan, Irvine, CA, United States) ( U.S. National Library of Medicine, 2021 ; Wolf et al, 2007 ). Notably, DFMO has a significant and promising inhibitory effect on diverse cancers, such as leukemia ( Bacchi et al, 1980 ; Xie et al, 2008 ; Casero and Woster, 2009 ; Alhosin et al, 2020 ), skin cancer ( Elmets and Athar, 2010 ), breast cancer ( Xu et al, 2008 ), prostate cancer ( Arisan et al, 2014 ) and pancreatic cancer ( Mohammed et al, 2014 ), cervical, small-cell lung cancer and melanoma ( Levin and Ellingson, 2018 ; Levin et al, 2018 ), gastric cancer ( Aziz et al, 2020 ), colorectal cancer ( Gutierrrez et al, 2019 ), neuroblastoma ( Lewis et al, 2020 ), glial tumors, such as malignant gliomas ( Levin et al, 2018 ), either as a single or in combination therapy ( Wallace and Fraser, 2004 ). DFMO has anabolic, wound-healing and immuno-enhancing actions.…”
Section: Introductionmentioning
confidence: 99%
“…The L -enantiomer of DFMO is 20-times more likely to form an enzyme–inhibitor complex than the D -form ( Qu et al, 2003 ), but the D -form is suggested as less toxic ( Levenson and Shaked, 2003 ). In order to overcome limitations, structural modifications and/or a combination therapy with other drugs is recommended to achieve optimal treatment outcomes ( Creaven et al, 1993 ; Alexiou et al, 2017 ; Li et al, 2019 ; Alhosin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%